Використання нейронних мереж для виявлення та класифікації шахрайських повідомлень у електронній пошті - Вельма, І. Ю. (ХНУРЕ, 2024)
In today's digital world, email phishing has become a serious threat to users and organizations. Malicious actors employ various methods and techniques to deliver fraudulent messages, attempting to deceive recipients and gain access to their confidential data or financial resources. Consequently, there is a need for effective methods of detecting and classifying phishing emails.
Keywords: шахрайські повідомлення; електронна пошта